The role of biotechnology during COVID-19 - Garro-Monge, Giovanni (2022)
Biotechnology is the application of science and technology to living organisms, as well as to parts, products, and models to alter living or non-living materials for the production of knowledge, goods, and services that benefit society. Precisely, this branch of science merges two of the most relevant areas that can provide valuable tools to help us fight against the SARS-CoV-2 pandemic. Among them are the applications of medical and plant biotechnology for the creation of a vaccine against the virus, where various institutions and biotechnology companies worldwide such as Pfizer and Medicago present promising results that are advancing towards advanced preclinical phases. Apart from this, various institutions have used alternative biotechnological techniques such as CRISPR gene editing to provide an alternative solution, such as Stanford University. However, the pandemic will also affect the economy, through which biotechnology can be of use especially in agricultural-based economies through advances in plant and food science. Precisely, at the national level for Costa Rica, it is estimated that the pandemic will have the highest impact in history on the economy of the Central American region. This will particularly affect the agricultural sector, an area where biotechnology offers promising solutions through technical advice regarding vitro plants, agrochemicals, and the most efficient and controlled use of resources. In short, today, more than ever, it is possible to demonstrate the importance of science, research and development and the fusion with the technologies offered by biotechnology to solve this global health and economic crisis.